Microcomputers for information resources management : a guide to the VITA system - Gariott, Gary L. (Volunteers in technical assistance ArlingtonUS, 1984)
Defines some of the terms and concepts common to all computer systems. Discusses basic computer operations such as creating, storing, & editing of files and programs. Outlines procedures used to maintain and operate VITA's bibliographic database and skills bank. These include data entry and database searching. Includes helpful guidelines for persons selecting a computer system and software package(s).